Social Capital and Communication Systems of Ettawa Goat Breeders in Purworejo Regency - Handaka, Tatag; Wahyuni, Hermin Indah; Sulastri, Endang; Wiryono, Paulus (Universitas Negeri Semarang, 2015)
The purpose of this study is to determine the social capital and communication system of Ettawa goat breeders (Peranakan Ettawa/PE) Kaligesing race in Purworejo. The study used the theory of social capital and communication systems in the perspective of Niklas Luhmann. The method of this study employed ethnography. Social capital of breeders is developed within farmersâ groups (Poktan). The existing social capitals in Poktan include trust, network, and norms. Social capital of trust is seen in the management of membership dues/contribution, poktan board transparency, division of work, and goat farming with nggaduh system. Network appears in the cooperation between Poktan with other Poktan, instructors/educator, traders/markets, universities, villages and districts. Norms are seen in the agreement on the division of dues, waragan group, and the breeders who use goats as debt guarantee and youth Poktan rules that prohibit breeders to sell the goats before lambing.